Felon Fights: Masculinity, Spectacle and Suffering - Tomsen, Stephen (2011)
Felony Fights is a website and set of DVDs depicting ‘no rules’ combat between male former convicts and a range of opponents. In these, the spectacle of violence serves to obscure the profoundly unequal relations of power that shape their production and viewing appeal. In Felony Fights, embodied marginality and poverty are presented as evidence of the animal brutality and the carceral character of the fighters. This resonates with populist explanations for criminality and male violence, and the punitive sentiments that are linked to law and order thinking about the failure of the penal system to adequately punish and inflict suffering on dangerous criminals.Sydney Institute of Criminology; School of Social Sciences at the University of Western Sydne